Activities of daily living amongst inmates of home for aged in Nagpur, Maharashtra, India: a cross sectional study - Jadhao, Ashok R.; Ghongte, Pravin R.; Ughade, Suresh N. (International Journal of Research in Medical Sciences, 2017)
Background: Although persons of all ages may have problems performing the Activities of Daily Living (ADL), prevalence rates are much higher for the elderly (65 years and over) than for the non-elderly. Elderly population face many problems. They become economically dependent on family for their basic needs and health care. Due to nuclear family norm, there is no place for elderly parent who feel alone and insecure. The study was undertaken to assess activities of daily living and reasons for admitting in home for aged amongst them. Objectives of present study were to assess the activities of daily living (ADL) and to identify the reasons for admitting in home for aged, in two homes for aged in Nagpur city, Central India. Methods: A cross sectional study was undertaken in two homes for aged namely Panchvati Vridhashram, Umred road and Home for aged, Untakhana, Nagpur, Maharashtra, India. Total 176 study subjects had consented for participation in study. Results: Mean age of study subjects was 73.47±6.06 year ranging from 61 to 90 years. Proportion of female inmate was 55.11%. Around one-fifth of study subjects (19.32%) were illiterate. Significantly more illiterate study subjects were of female gender (chi- square=5.78, d.f.=1, P=0.016). Mean duration of stay in home for aged was 5.29±3.29 years with the range of 9 months to 17 years. Number of study subject’s dependent for at least one ADL was 37 (21.02%). Amongst dependents 32 (18.8%) inmates were partially dependent with ADL score of 1-5 and only 5 (2.85%) inmates were totally dependent with ADL score of 6-12. The proportion of inmates with dependency for at least one activity of activities of daily living increases as the age increases. Positive liner trend was observed between age and dependency (r=0.1971, P=0.0087). Conclusions: Prevalence of ADL dependency was 21.02% among the inmates of home for aged. Dependency for activities of daily living increases with increase in age. Major reasons for admission to the home for aged were - no one to look after, strained relation with family members and economic constraints. There is need for economic assistance through social security to economically dependent inmates.